Agreement between the United Kingdom of Great Britain and Northern Ireland and the Swiss Confederation on Admission to the Labour Market for a Temporary Transitional Period following the withdrawal of the United Kingdom from the European Union and the Free Movement of Persons Agreement, London, 10 July 2019. ([2019-07-18]) - Unknown
No abstract available